Purely electronic zero-phonon line as the foundation stone for high-resolution matrix spectroscopy, single-impurity-molecule spectroscopy, and persistent spectral hole burning. Recent developments: Spectroscopy in Cryocrystals and Matrices - Rebane, Karl K. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2003)
A few examples of recent progress in the study and applications of purely electronic zerophonon line (ZPL) and its offshoots are briefly considered: new experimental values of the narrowestZPL; time-and-space-domain holography in the femtosecond domain, and the realization of a femtosecond Taffoli gate by it; single-impurity-molecule spectroscopy, its relation to single-photoninterference and to the realization of quantum computing; the promises of quantum computing compared to what has already been done in holography.